A narrative of the captivity of Nehemiah How in 1745-1747; - How, Nehemiah, 1693-1747.; Paltsits, Victor Hugo, 1867-1952, editor.; Pals'ts, Victor Hugo, 1867-1952, ed. (Cleveland, The Burrows brothers company, 1904)
Contains reprint of original t.-p. Mode of access: Internet.